THE USE OF FORAMINIFERA FOSSILS FOR RECONSTRUCTING THE YOGYAKARTA GRABEN, YOGYAKARTA, INDONESIA - Didit Hadi Barianto; Pentatok Kuncoro; Koichiro Watanabe (Journal of Applied Geology, 2015)
The Yogyakarta region is located in the southeastern part of Central Java, Indonesia. The region forms an elongated northeast – southwest-trending central depression bordered by two parallel faults in the west and east. These major faults divided the area into three parts, including the western, central and eastern parts. Herein, we investigate the relative uplift rate of the each part by using planktonic and benthonic foraminiferas. The foraminifera will show the initial position/datum of each part before uplift. Over sixty samples (primarily limestones and marls) were taken for this research. The uplift rates of each part were different and created a depressed block control by way of parallel faults. Based on foraminifera fossil observations, each block was in the same depositional environment (inner neritic) during N9. The present positions indicate that the western part was uplifted higher than the others, with this part being uplifted more than 590 meters. The central part was uplifted less than 120 meters, and the eastern part was uplifted above an altitude of 170-300 meters. Keywords: Foraminifera fossil, planktonic, benthonic, graben, uplift